Measurement and analysis of restitution coefficient between maize seed and soil based on high-speed photography - Jinwu, Wang; Han, Tang; Jinfeng, Wang; Dongxuan, Jiang; Xin, Li (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The restitution coefficient is an important elementary physical parameter related to the research and development of agricultural machinery. The kinematic model of maize seed in the falling and impacting processes was developed to measure the restitution coefficient between maize seed and soil. A test bench for measuring the restitution coefficient was designed and built referred to the theory of mirror reflection. The velocities for impacting maize seed were measured and analyzed in a three-dimensional space via high-speed photography, and then restitution coefficients of in different impact conditions were obtained. On this basis, this study took flat dent seed and round seed as samples. Single factor tests were conducted to analyze the influences of these factors on the restitution coefficient. The impact angle, falling height, soil compaction, soil moisture, maize moisture content and different parts of seed were selected as test factors. The corresponding regression equations were obtained by analysis. The results showed that, as the impact angle was bigger than 25°, the restitution coefficient increased with the increase of impact angle. The restitution coefficient had a linear decreasing trend with the increase of falling height. As the soil compaction strength was 200-350 kPa, the restitution coefficient increased with the increase of soil compaction. As the soil compaction strength was larger than 350 kPa, the changing trend of the restitution coefficient was relatively stable. As the soil moisture content was 13.5%-18%, the restitution coefficient decreased with the increase of soil moisture. As the soil moisture content was 18%, the restitution coefficient was the minimum. As the maize moisture content was 11%-16%, the restitution coefficient decreased with the increase of maize moisture content. The rotational motion always occurred in falling process of flat dent seed and round seed. The probabilities of crown part and lateral part of maize seed impacting with soil were the highest, and the restitution coefficient between crown part and soil was higher than that of other parts in the same condition. Keywords: maize seed, soil, restitution coefficient, mirror reflection, high-speed photography, measurement DOI: 10.3965/j.ijabe.20171003.2173 Citation: Wang J W, Tang H, Wang J F, Jiang D X, Li X. Measurement and analysis of restitution coefficient between maize seed and soil based on high-speed photography. Int J Agric & Biol Eng, 2017; 10(3): 102–114.